Insights on the Thermal and Physical Stability of the Modified Polymerizable Liposomes for Improved Photoactivity - Poornima, Kalyanram; Noor, Hussein; Amit, Tiwari; Anju, Gupta (International Journal of Lipids, 2020)
We investigated physical steric and thermal stability effects induced by cholesterol and polyethylene glycol (PEG) in liposomes encapsulated with riboflavin. The composition of liposome was varied systematically to decipher the individual and combined effects of cholesterol and PEG on the stabilization of liposomes, specially the photopolymerizable liposomes for their potential applications in photo-treatments. Our results indicate that inclusion of PEG in the lipids enhances the steric stabilization by adopting a brush-like regime that prevents the agglomeration of encapsulated liposomes. A mechanistic differential scanning calorimetry studies reveal the phase transitions and enthalpy changes in the lipid bilayer due to the presence of cholesterol suggesting its role in regulating membrane fluidity. Supporting in- vitro studies confirm the efficacy of PEGylated formulations encapsulating riboflavin.
Keywords: Drug carriers; Thermal analysis; Polymer; Lipid bilayer; Steric stabilization; Cholesterol